FINANCIAL ANALYSIS OF PADDY MOBILE BUSINESS IN GANDAPURA SUB-DISTRICT BIREUEN - Nur, T. M.; Mulyadi, E. (JURNAL KEBANGSAAN, 2013)
The aims of this research is to analyze the feasibility of paddy mobile business in Gandapura Subdistrict- Bireuen. The method on it is done by census method. The results showed that the average paddy mobile business including characteristics of age is 33 years, 9 years of education, experience in paddy mobile business is 3 years, the number of family dependents is 4 people, and family income of paddy mobile business around Rp. 1300000-1600000 per month. In paddy mobile business, first investment is required Rp. 22,911,000, -, operating costs Rp. 3.504.000,- per month, and the cost of machinery and equipment depreciation is 179. 750,- per month. The average of grinded paddy samples is 1566.66 kg per month, and the average revenue received by paddy employersâ mobile business samples is 940 kg per month. While the average net income received by paddy employers mobile business is Rp. 2,238,250, -. Feasibility analysis results obtained, the value of a positive NPV shows that the value is Rp. 15,528,171.5. the value NBCR value greater than one (>1) is 1.68. IRR values> 5% is 9.165%. And PBP faster in the 15 months and 7 days, therefore paddy mobile business is feasible to run. Key words : Paddy mobile, Financial analysis